Nutritional interventions to improve recovery from postoperative ileus. Issue 5 (September 2018) - Smeets, Boudewijn J.J.; Luyer, Misha D.P.
Abstract : Purpose of review: Postoperative ileus (POI) is an important contributor to postoperative morbidity. However, postoperative outcomes have improved by enhanced recovery after surgery (ERAS) programs. Enteral nutrition is an essential part of ERAS and many studies suggest a therapeutic effect of nutrition on POI. Recent findings: Early postoperative enteral nutrition has been shown to reduce various complications, including POI, although studies are heterogeneous. Experimental studies suggest that composition and timing of the enteral feed is important for the potential beneficial effects: lipid-enriched nutrition given just before, during, and directly after surgery was most effective in reducing POI in an experimental setting. In a clinical study in patients undergoing advanced rectal cancer surgery, direct start of enteral tube feeding reduced POI. Conversely, perioperative lipid-enriched enteral nutrition did not reduce POI in patients undergoing colorectal surgery with an ERAS protocol. Summary: POI is common and remains an important determinant of postoperative recovery following colorectal surgery. Nutrition is a potential therapeutic means to reduce POI. Timing and composition of the enteral feed have been shown to be essential for the beneficial effects of enteral nutrition in an experimental setup. However perioperative lipid-enriched nutrition does not reduce POI in patients undergoing colorectal surgery with an ERAS protocol.